Electrical delay line multiplexing for pulsed mode radiation detectors - Vinke, Ruud (Phys Med Biol, 2015)
Medical imaging systems are composed of a large number of position sensitive radiation detectors to provide high resolution imaging. For example, whole-body Positron Emission Tomography (PET) systems are typically composed of thousands of scintillation crystal elements, which are coupled to photosensors. Thus, PET systems greatly benefit from methods to reduce the number of data acquisition channels, in order to reduce the system development cost and complexity. In this paper we present an electrical delay line multiplexing scheme that can significantly reduce the number of readout channels, while preserving the signal integrity required for good time resolution performance. We experimented with two 4 × 4 LYSO crystal arrays, with crystal elements having 3 mm × 3 mm × 5 mm and 3 mm × 3 mm × 20 mm dimensions, coupled to 16 Hamamatsu MPPC S10931-050P SiPM elements. Results show that each crystal could be accurately identified, even in the presence of scintillation light sharing and inter-crystal Compton scatter among neighboring crystal elements. The multiplexing configuration degraded the coincidence timing resolution from ~ 243 ps FWHM to ~272 ps FWHM when 16 SiPM signals were combined into a single channel for the 4 × 4 LYSO crystal array with 3 mm × 3 mm × 20 mm crystal element dimensions, in coincidence with a 3 mm × 3 mm × 5 mm LYSO crystal pixel. The method is exible to allow multiplexing configurations across different block detectors, and is scalable to an entire ring of detectors.